Proximal Gauss-Newton method - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter we extend the solvability of penalized nonlinear least squares problems using the proximal Gauss–Newton method. Moreover, a numerical example validating the theoretical results is also presented.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: proximal Gauss–Newton method; penalized nonlinear least squares problems; local convergence; WOS(2)